2008
DOI: 10.2298/jsc0809815m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, NMR, DFT and antimicrobial studies of Zn(II) complexes with N-benzyloxycarbonyl-S-alanine

Abstract: In this study, the first complexes of Zn(II) with the N-benzyloxycarbonyl-S-alaninato ligand (N-Boc-S-ala) were synthesized. The new complexes were characterized by elemental analysis, conductometric measurements, IR, 1 H-NMR, 13 C-NMR and 2D-NMR spectroscopy. On the basis of the experimental data, tetrahedral geometry of the Zn(II) complexes was proposed. A very good agreement between the NMR and DFT calculated data was obtained. Investigation of antimicrobial activity of the newly synthesized complexes was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The oxidation of purpurin with hydrogen peroxide in the presence of cobalt(II) as a catalyst in a carbonate buffer solution gives a colorless product. 19 It was observed that a small amount of arginine inhibits this reaction. The rate of the reaction is inversely proportional to the concentration of this amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of purpurin with hydrogen peroxide in the presence of cobalt(II) as a catalyst in a carbonate buffer solution gives a colorless product. 19 It was observed that a small amount of arginine inhibits this reaction. The rate of the reaction is inversely proportional to the concentration of this amino acid.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the 1 H NMR spectrum of ligands showed a signal at δ 8.65 ppm which is caused by the NH group. In complexes this signal was shifted to higher field in the spectra[38,39].There are signals at 7.87 and 7.88 ppm in the 1 H NMR spectrum of ligands were assigned to azomethine proton (H-C=N) these signals shifted to upfield due to the participation of 944 IJBPAS, May, 2019, 8(5)…”
mentioning
confidence: 99%